The Effect of Price on the Decision to Purchase Ethiopian Airlines Tickets at PT Aviaventura Aero Agency Jakarta - Saputri, Rasyiqah Zatalini; Putra, Dian Berliansyah; Aryadi, Heri; Indra, Natal (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Ethiopian Airlines is one of the airlines in PT Aviaventura Aero Agensi Jakarta. With increasing competition in the aviation industry, determining the right price is one of the key factors in attracting consumers. This study aims to determine the effect of price on purchasing decisions for Ethiopian Airlines tickets at PT Aviaventura Aero Agensi Jakarta. The research method used is quantitative descriptive analysis using primary data in the form of questionnaires. The population in this study were customers of PT Aviaventura Aero Agensi Jakarta. While the sample used was random sampling with a total of 50 respondents. Based on the results of the study, it can be concluded that price influences purchasing decisions by 66.7% while the remaining 33.3% is influenced by other factors. And the results of the regression equation test can be obtained Y = 2.825 + 0.896X which means that if the quality-of-service increases by 1 (one) value, there will be an additional reduction in purchasing decisions of 0.896.